Dot size variability induced changes in the optical absorption spectra of interdiffused quantum dot systems - Sinha, Shambhu Sharan Kumar; Kumar, Subindu; Das, Mukul Kumar (Applied physics. A, Materials science & processing, 2019)
In this work, we have quantified the effects of dot size variability on the interband optical absorption spectra of interdiffused III–V quantum dot (QD) systems through analytical models which agree well with experimental data. The variability function induced due to inhomogeneous nature of dot size distribution has been considered to be Gaussian in nature, where individual dots have been assumed to be lens-shaped having inhomogeneous material composition inside the dot. This is necessary to consider any realistic interdiffused system. Such an assumption is not in line-up with the conventional methodologies reported earlier on the subject, where the QD composition was considered to be homogeneous, presenting an ideal or quasi-ideal situation which may be applicable only for dot structures in absence of interdiffusion. Moreover, for the first time, the effects of dot size variability and interdiffusion on the optical spectra of QD systems have been analysed in the same platform. The effects of dot size deviation, QD aspect ratio, core group III content inside the dot, standard deviation, and so on, on the optical absorption spectra have been demonstrated.